Development of a position statement for Australian critical care nurse education. Issue 4 (July 2019) - Gill, Fenella J.; Lin, Frances; Massey, Deborah; Wilson, Lorraine; Greenwood, Melanie; Skylas, Katina; Woodard, Mark; Tembo, Agness; Mitchell, Marion; Gullick, Janice
Abstract: Position statements are used by large organisations such as the Australian College of Critical Care Nurses to publically present an official philosophy or beliefs and to propose recommendations. Position statements are increasingly used by health departments and healthcare facilities to allocate resources and to guide and audit nursing practice, yet there are limited resources on the process of their development. A position statement should help readers better understand the issue, communicate solutions to problems, and inform decision-making. It should be supported by the highest level of evidence available and reflect the organisation's governing objectives and goals. In this article, we describe the structured approach used to develop a position statement for Australian critical care nurse education. The formation of an expert advisory panel, synthesis of available evidence using Whittemore and Knafl's integrative review methodology, use of Donabedian's structure-process-outcomes quality framework as a theoretical approach, and multiple layers of consensus building and consultation enabled the development of an important critical care document and informed an implementation plan. The framework and processes we have outlined in this discussion article may provide a useful starting point for other professional organisations wishing to develop similar position statements.